Photolysis study of octyl p-methoxycinnamate loaded microemulsion by molecular fluorescence and chemometric approach - Silva Do Nascimento, Danielle (2018)
Octyl p-methoxycinnamate (OMC) is one of the most widely used sunscreen agents. However, the efficiency of OMC as UV filter over time is affected due to the formation of the cis-isomer which presents a markedly lower extinction coefficient (εcis = 12,600 L mol− 1 cm− 1 at 291 nm) than the original trans-isomer (εtrans = 24,000 L mol− 1 cm− 1 at 310 nm). In this work, a novel carrier for OMC based on an oil-in-water microemulsion is proposed in order to improve the photostability of this sunscreen. The formulation was composed of 29.2% (w/w) of a 3:1 mixture of ethanol (co-surfactant) and decaethylene glycol mono-dodecyl ether (surfactant), 1.5% (w/w) of oleic acid (oil phase) and 69.2% (w/w) of water. This microemulsion was prepared in a simple way, under moderate stirring at 25 °C and using acceptable, biocompatible and accessible materials for topical use. OMC was incorporated in the vehicle at a final concentration of 5.0% (w/w), taking into account the maximum permitted levels established by international norms. Then, a photolysis study of the loaded formulation was performed using a continuous flow system. The direct photolysis was monitored over time by molecular fluorescence. The recorded spectra data between 370 y 490 nm were analyzed by multivariate curve resolution-alternating least squares algorithm. The kinetic rate constants corresponding to the photolysis of the trans-OMC were calculated from the concentration profiles, resulting in 0.0049 s− 1 for the trans-OMC loaded microemulsion and 0.0131 s− 1 for the trans-OMC in aqueous media. These results demonstrate a higher photostability of the trans-OMC when loaded in the proposed vehicle with respect to the free trans-OMC in aqueous media.